CO2, water, and sunlight to hydrocarbon fuels: a sustained sunlight to fuel (Joule-to-Joule) photoconversion efficiency of 1%. Issue 9 (21st May 2019) - Sorcar, Saurav; Hwang, Yunju; Lee, Jaewoong; Kim, Hwapyong; Grimes, Keltin M.; Grimes, Craig A.; Jung, Jin-Woo; Cho, Chang-Hee; Majima, Tetsuro; Hoffmann, Michael R.; In, Su-Il
Abstract : Cu–Pt bimetallic nanoparticles deposited over blue titania exhibiting record photoconversion efficiency for CO2 photoreduction into fuels. Abstract : If we wish to sustain our terrestrial ecosphere as we know it, then reducing the concentration of atmospheric CO2 is of critical importance. An ideal pathway for achieving this would be the use of sunlight to recycle CO2, in combination with water, into hydrocarbon fuels compatible with our current energy infrastructure. However, while the concept is intriguing such a technology has not been viable due to the vanishingly small CO2 -to-fuel photoconversion efficiencies achieved. Herein we report a photocatalyst, reduced blue-titania sensitized with bimetallic Cu–Pt nanoparticles that generates a substantial amount of both methane and ethane by CO2 photoreduction under artificial sunlight (AM1.5): over a 6 h period 3.0 mmol g −1 methane and 0.15 mmol g −1 ethane are obtained (on an area normalized basis 0.244 mol m −2 methane and 0.012 mol m −2 ethane), while no H2 nor CO is detected. This activity (6 h) translates into a sustained Joule (sunlight) to Joule (fuel) photoconversion efficiency of 1%, with an apparent quantum efficiency of φ = 86%. The time-dependent photoconversion efficiency over 0.5 h intervals yields a maximum value of 3.3% ( φ = 92%). Isotopic tracer experiments confirm the hydrocarbon products originate from CO2 and water.